(untitled) (Health Renaissance, 2011)
Introduction: The unmet need for family planning is a very useful tool in measuring and predicting the contraceptive needs of a population. Seventeen percent of all married women would prefer to avoid pregnancy but are not using any form of family planning. In less developed countries, about one forth of pregnancies is unintended. Objective: To determine the level of unmet need for family planning and evaluate the factors that influences the unmet needs in Married Women of Reproductive Age (MRWA). Methods: A cross-sectional study of 410 women attending the immunization clinic of B.P.Koirala Institute of Health Sciences, a teaching hospital in Dharan was carried out over 3 months. Results: MRWA had 22%, 15% and 8% unmet needs for family planning, spacing and limiting births respectively. Health concerns and side effects (30.5%), husband and family opposition (14%), uncertainty about child bearing (12.2%) and inconvenience (10%) were among the major constraints to the use of contraception. Unmet need has significant association between parity & education. Age and family type had no significant effect on unmet needs. Conclusion: In spite of high level of awareness about family planning method, a significant level of unmet need exists among women of reproductive age. Keywords: unmet needs; family planning; married women of reproductive age; MRWA DOI: http://dx.doi.org/10.3126/hren.v9i3.5581 HR 2011; 9(3): 148-151